Currículo na Educação Infantil: Um estudo no Centro Municipal de Educação Infantil CMEI Irmã Lucília - SANTOS, Leidiane Silva (Universidade Federal do Tocantins, 2021)
This research aims to analyze how the Hidden Curriculum influences the learning of children at the Municipal Center for Early Childhood Education Irmã Lucília (CMEI), located in Arraias-TO. The researcher's interest arose when she realized the diversity of pedagogical practices carried out in the teaching and learning process in Early Childhood Education. Barreto (1998), Moreira (2011), Silva (2010), Sacristán (1998), among others, in addition to the Federal Constitution (1988) and the Law of National Education Guidelines and Bases (1996) were used as the theoretical basis. We started the research in June 2019, carried out the field research in November 2019, ending the research in September 2020. This way, the qualitative approach was used to carry out the research, the research subjects were teachers, monitors, coordinator and children from two classes of Pre II of the Municipal Center for Early Childhood Education - CMEI Irmã Lucília, in Arraias - TO, totaling 54 participants. The instruments for data collection were the questionnaire, analysis of the teaching plan of the teachers and the children's notebooks, systematic observation of classes in the classes of Pre II “D” and Pre II “C”. The research pointed out that the hidden curriculum is present in the actions carried out by the teachers such as: videos, films, in moments of prayer, activities applied during class time, without containing specifications in the plan in the classroom, in the chair of thought (punishment), in the moments when children are separated into groups, according to behavior. And that the hidden curriculum contributes to children's learning, knowledge of rules and norms, in addition to attitudes and reflections that are essential for children to understand their identity and autonomy.